The effect of opposing notch geometry on the tensile strength of adhesively bonded single-lap joints. Issue 8 (6th April 2020) - Çam, Salim; Özel, Adnan
Abstract : Purpose: This study aims to investigate the effect of opposing notches formed on the adherends on the tensile strength of an adhesively bonded single-lap joint. Design/methodology/approach: Different notch geometries were constructed on adherends and evaluated by using the Taguchi method to obtain optimum notch geometry. Then finite element analysis was conducted considering optimum notch geometries by using the cohesive zone model. Lastly, finite element analysis results were validated experimentally. Findings: Experimental and numerical studies revealed that notches formed on adherends increased the tensile strength of the joint. The failure load of the Type-III joint, where the highest increase was observed, increased by 15 per cent. In addition, it was found that the notch shape, length, depth and distance to the overlap area had significant effects on the failure load of the joint. Originality/value: This study shows that higher joint strengths can be accomplished by using the same joint configuration by notching adherends.